A comparative study of the methods for establishing a local sustainable building rating system - Zhuoyao Wang; Zhu Wang; Zhenlan Qian (International Association of Lowland Technology, 2020)
Sustainable building rating systems (SBRSs) play an important role in promoting the development of sustainable buildings. As SBRSs need to adapt to the local context, many countries and regions have made efforts in recent years to establish their local SBRSs. However, there is no consensus on how to set up a local SBRS. The purpose of this paper is to identify the main steps in and methods for developing a local SBRS and to provide a reference for subsequent research on establishing such a rating system. Therefore, this paper reviews and compares the relevant literature on the regional development of SBRSs. Four main development stages are identified: the selection of indicators and categories, the establishment of a weighting system, conversion into the rating system, and verification and modification. Accordingly, the methods commonly included in the four stages are identified and discussed, and the applicability and limitations of the methods are determined through comparative analysis. Finally, this paper proposes the future research direction related to the establishment of a future SBRS.